Asymptomatic malaria and nurturing factors in lowlands of Ethiopia: A community based cross-sectional study - Endale Mengesha; Meseret Dessalegne Zerefa; Habteyes Hailu Tola (Public Library of Science (PLoS), 2022)
Although asymptomatic malaria cases are reservoirs of malaria parasites, there is limited evidence on the burden and nurturing factors in malaria endemic areas during dry season. Thus, this study aims to determine the prevalence of asymptomatic malaria infection and nurturing factors in endemic areas of Ethiopia during dry season.A community based cross-sectional study was conducted in malaria endemic areas in Ethiopia. Six villages with a total of 1,366 households from three malaria endemic regions of Ethiopia were selected by stratified random sampling method. One asymptomatic member of the household was randomly selected from each household. A structured questionnaire was used to collect data on socio-demographic and other factors. Finger prick blood samples for malaria rapid diagnostic test (RDT) and blood film were collected and examined. Multivariable logistic regression model was used to determine the nurturing factors with asymptomatic malaria infection. The prevalence of asymptomatic malaria infection was 7.7% with both blood film microscopic examination and malaria RDT. Plasmodium falciparum was the predominantly observed type of malaria species (48.0%). The presence of bodies of water around the households (adjusted odds ratio (AOR = 5.4; 95% CI (2.7 ─ 9.7); p < 0.000), infrequent indoor residual spray (IRS) applied four to six months ago (AOR = 3.5; 95% CI (1.0─11.6); p = 0.045) and more than six months (AOR = 5.2; 95% CI (1.3─20.5); p = 0.019) and personal protection measure for malaria prevention (LLIN, repellent and clothing) (AOR = 0.41; 95% CI (0.2 ─ 0.9); p = 0.028) were associated significantly with asymptomatic malaria infection. The prevalence of asymptomatic malaria infection during dry season was considerable. Strong interventions that target stagnant bodies of water, infrequent household IRS spray and personal protection measure for malaria prevention is required to decrease asymptomatic malaria infection during dry season.